Development of alternative environment friendly nickel and gold plating baths - Gezerman, A. O.; Corbacioglu, B. D. (TAYLOR & FRANCIS LTD, 2015)
In the metal plating industry, nickel and gold plating baths are used, which contain toxic materials and cause wastewater problems. Despite these disadvantages, there is a strong need for both these types of metal plating because of their aesthetic properties. However, until now, nickel plating has not been used in conjunction with gold plating because nickel plating baths contain sulphates. In this study, gold plating on a nickel plated surface is investigated using baths containing acetylacetonate salts. The physical parameters of the plated materials, which were favourable, were determined by hydrogen embrittlement tests, visible region spectrophotometry and the Charpy impact test.
Keywords: Gold cyanide; Nickel(II) acetylacetonate; Dimethylgold(III) acetylacetonate; Embrittlement; CORROSION-RESISTANCE; ELECTRODEPOSITION; NI; NANOCOMPOSITE; DEPOSITION; COATINGS; ALLOY; ACETYLACETONATE; ELECTROLYTE; RECOVERY; Materials Science